الإطار القانوني للاتفاق العالمي من أجل الهجرة الآمنة والمنظمة والنظامية - غريب، أليسار; العمر، أحمد (جامعة البعث, 2021)
أضحت قضايا الهجرة من القضايا الدولية المعاصرة التي تصدرت مناقشات المجتمع الدولي نتيجة سلسلة من الأزمات الإنسانية، وهذا ما دفع الدول إلى عقد اجتماع دولي رفيع المستوى برعاية الجمعية العامة للأمم المتحدة بشأن التحركات الكبيرة للاجئين والمهاجرين في 19 سبتمبر 2016 لمعالجة قضايا الهجرة، والذي نتج عنه اعتماد الاتفاق العالمي من أجل الهجرة الآمنة والمنظمة والنظامية. يحاول هذا البحث بيان الطبيعة القانونية للاتفاق العالمي وإمكانية تنفيذ أهدافه وقابليته ليصبح إطارا قانونيا ملزما للدول، قد أثارت طبيعته العديد من التساؤلات بوصفه صادر بقرار من الجمعية العامة هذا من جهة، ومن جهة أخرى كونه جاءت قيمته من قيمة محتواه من خلال تأكيده على المبادئ والمعايير الواردة في المعاهدات الدولية الملزمة. Migration issues have become a contemporary international issue that has dominated the international community's discussions as a result of a series of humanitarian crises, prompting states to hold a high-level international meeting sponsored by the UN General Assembly on the large movements of refugees and migrants on September 19, 2016 to address migration issues, which resulted in the adoption of the Global Compact for Safe, Orderly and Orderly Migration. This research attempts to demonstrate the legal nature of the Global Agreement and the possibility of implementing its objectives and its viability to become a binding legal framework for States, the nature of which has raised many questions as a decision of this General Assembly on the one hand, and on the other hand, because it came from the value of its content by emphasizing the principles and standards contained in binding international treaties.
Keywords: ظاهرة الهجرة -- المعاهدات الدولية -- القانون الدولي